2011
DOI: 10.1055/s-0031-1273217
|View full text |Cite
|
Sign up to set email alerts
|

Der frühe postnatale Gewichtsverlauf als Prädiktor einer Frühgeborenenretinopathie

Abstract: The high predictive value of the WINROP-algorithm was confirmed in our population of Swiss preterms. This instrument has the potential to simplify the current ROP screening procedure. Accordingly, the amount of ophthalmoscopies could be reduced significantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The sensitivity of WINROP to predict patients at high risk of treatment-demanding ROP was only 64.7% in the current study, which is not as high as in previous studies. [13][14][15][16]18 In addition, it missed all the treatment-demanding ROP in infants with a BW more than 1,250 g and a GA more than 30 þ0 weeks. This shows that the WINROP is not an appropriate screening tool for Taiwan, a middle income, moderately developed country, especially for predicting severe ROP in larger preterm infants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity of WINROP to predict patients at high risk of treatment-demanding ROP was only 64.7% in the current study, which is not as high as in previous studies. [13][14][15][16]18 In addition, it missed all the treatment-demanding ROP in infants with a BW more than 1,250 g and a GA more than 30 þ0 weeks. This shows that the WINROP is not an appropriate screening tool for Taiwan, a middle income, moderately developed country, especially for predicting severe ROP in larger preterm infants.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported good efficacy of this newly developed screening tool. [13][14][15][16] However, the data gathered so far mainly includes highly developed countries, such as Sweden and the United States, and some data are currently available for moderately or lowdeveloped countries, such as Mexico, Korea, and China. [17][18][19] In such countries, ROP in larger preterm infants is more common than in highly developed countries, and whether or not WINROP can predict severe ROP in these countries is unknown.…”
mentioning
confidence: 99%
“…Recently, clinical prediction models to early identify patients in risk of ROP were presented. WINROP [29][30][31] and PINT-ROP 32 were presented using postnatal longitudinal weight gain measurements. ROPScore, by the other hand, uses the BW and the weight measured at completed 6 weeks of life as weighted values in the final calculation of the score.…”
Section: Discussionmentioning
confidence: 99%
“…The WINROP monitoring tool was introduced and evaluated with satisfactory results in different preterm populations worldwide [13,15,16]. These studies have all retrospectively included both very and extremely preterm infants.…”
Section: Introductionmentioning
confidence: 99%